Design, fabrication and thermal performance of a novel ultra-thin loop heat pipe with printed wick structure for mobile electronics cooling. (5th January 2022) - Chen, Anqi; Jiang, Fan; Dong, Jiajia; Chen, Jeffrey; Zhu, Yuan
Highlights: The proposed ultra-thin loop heat pipe is manufactured by a novel print wick structuring process. Optimized wick distribution and filling ratio. Overall size is 70 mm × 30 mm × 0.3 mm. Effectively transport a maximum heat flux of 3 W / c m 2 with a minimum thermal resistance of 1.03 °C / W . Low sensitivity to gravity. Abstract: Ultra-thin loop heat pipe (UT-LHP) is a high-performance heat transfer component that satisfies the requirement of thermal management problems in miniaturized electronic devices. In this study, a novel UT-LHP with capillary wick structures is developed for mobile electronics cooling. By using a novel print wick structuring process on copper substrates, the total thickness of the UT-LHP can be decreased to only 0.3 mm. The effects of the filling ratio and wick structure distribution have been investigated to optimize the vapor–liquid circulation in the UT-LHP. The heat transfer performance of the UT-LHP has been evaluated under different heat loads and configurations. The minimal thermal resistance of the UT-LHP is 1.03 °C / W at a heat load of 3 W which corresponds to a heat flux of 3 W/cm 2 . It is confirmed that the proposed UT-LHP can transfer a heat load of up to 3 W with low sensitivity to gravity. The proposed novel UT-LHP is a promising thermal solution for high-performance mobile electronic devices.